North Carolina's criminal justice system - Knepper, Paul (Carolina Academic Press, 2011)
Crime -- Education and training -- The constitution -- Lawmaking -- Law enforcement -- Prosecution and defense -- Courts and adjudication -- Corrections -- Juvenile justice